2013
DOI: 10.1016/j.bpj.2013.05.064
|View full text |Cite
|
Sign up to set email alerts
|

Coiled-Coil Response to Mechanical Force: Global Stability and Local Cracking

Abstract: Coiled coils are important structural motifs formed by two or more amphipathic α-helices that twist into a supercoil. These motifs are found in a wide range of proteins, including motor proteins and structural proteins, that are known to transmit mechanical loads. We analyze atomically detailed simulations of coiled-coil cracking under load with Milestoning. Milestoning is an approach that captures the main features of the process in a network, quantifying kinetics and thermodynamics. A 112-residue segment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Anchors can be determined by prior thermodynamic sampling (e.g. by replica exchange[41,42]), by reaction path calculations [43,44], or by chemical intuition[34,45]. For example, studies of peptide folding and unfolding in an explicit solvent use only the backbone dihedral angles of the peptide as the coarse variables [42,46].…”
Section: Milestoningmentioning
confidence: 99%
See 1 more Smart Citation
“…Anchors can be determined by prior thermodynamic sampling (e.g. by replica exchange[41,42]), by reaction path calculations [43,44], or by chemical intuition[34,45]. For example, studies of peptide folding and unfolding in an explicit solvent use only the backbone dihedral angles of the peptide as the coarse variables [42,46].…”
Section: Milestoningmentioning
confidence: 99%
“…If their corresponding relaxation times are long compared to typical MD simulations of membranes (a few to hundreds of nanoseconds) then their sampling must be explicitly enhanced, or longer simulations must be conducted. The sampling of more than a single variable can be enhanced by methods such as TAMD [31], TAMC [32], Metadynamics [33] and Milestoning [34]. Milestoning has the advantage that it makes it possible to compute the kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…As the heptad is repeated, it forms a continuous hydrophobic patch located along a single face of the ␣-helix compatible with a tight intermolecular interaction between polypeptides with the same or similar heptad pattern (2). However, often polar or charged residues occupy the a and d positions, leading to local destabilization of the coiled-coil motif (2)(3)(4). By extension, when most or all of the a and d sites in consecutive heptads are occupied by polar residues, individual ␣-helices cannot be mutually stabilized through hydrophobic packing.…”
Section: Coiled-coil or Single ␣-Helical (Sah) Domain?mentioning
confidence: 99%
“…In a parallel vein, helix formation through E-K interactions, independent of alanine, was examined by Lyu et al (17) with 18-amino acid peptides with either (E 2 K 2 ) 4 or (E 4 K 4 ) 4 repeats. Although the composition was exactly the same for both peptides, CD and 1 H NMR data showed that the E 4 K 4 peptide has 65% helical content, whereas the E 2 K 2 peptide is essentially a random coil.…”
Section: Stability Of Er/k ␣-Helicesmentioning
confidence: 99%
“…It has been used previously with methods like Hyper-Dynamics, 11 MSM, 4 and Milestoning. 9 The advantage of frequent exchanges of information between networks and continuous space is the ability to identify "on-the-fly," regions that are poorly or oversampled. For example, the network analysis may identify an important transition (or an edge) for which only a few successful events were recorded.…”
Section: Introductionmentioning
confidence: 99%